Analisis Rasio Keuangan Dalam Menilai Kinerja Keuangan Pada Industri Kosmetik yang Terdaftar di BEI - Abdullah, Nur Hudaya; Agung Widhi Kurniawan; Nurman; Romansyah Sahabuddin; Andi Mustika Amin (CV. Lafadz Jaya, 2023)
The study aims to determine the financial performance of the cosmetic industry listed in IDX using the analysis of liquidity ratio and profitability ratio. This study uses a quantitative approach. The data source used in this study is secondary data and the data collection technique in this study is documentation. The population of this study is the cosmetic industry listed in IDX and sampling method using purposive sampling techniques, so the samples on this research are PT Kino Indonesia Tbk and PT Unilever Indonesia Tbk with the period from 2019 to 2021. The results of this study show that the analysis of liquidity ratio measured by current ratio and quick ratio at PT Kino Indonesia Tbk period from 2019 to 2021 is superior, it is show that the company is able to meet its current obligations. And analysis of profitability ratios measured by net profit margin and return on assets at PT Unilever Indonesia Tbk period from 2019 to 2021 has a superior value, it is show that the company is able to generate high net profit.